2017
DOI: 10.7567/apex.10.115801
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionless figure of merit and its efficiency estimation for transient response of thermoelectric module based on impedance spectroscopy

Abstract: The dimensionless figure of merit and its efficiency for the transient response of a Π-shaped thermoelectric module are estimated according to the theory of impedance spectroscopy. The effective dimensionless figure of merit is described as a function of the product of the characteristic time to reduce the temperature and the representative angular frequency of the module, which is expressed by the thermal diffusivity and the length of the elements used. The characteristic time required for achieving a higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…7,9 After an analysis of the frequency dependence of the impedance by a Nyquist diagram, the thermoelectric module is assumed to be a circuit possessing two resistances (R ohm and R TE ) and one capacitance (C TE ), 4,6,7,9 which are a sort of time lag of a first-order circuit. 12 We have introduced a suitable assumption for the module called the RC approximation such that the MEI term in Eq. (1) vanishes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,9 After an analysis of the frequency dependence of the impedance by a Nyquist diagram, the thermoelectric module is assumed to be a circuit possessing two resistances (R ohm and R TE ) and one capacitance (C TE ), 4,6,7,9 which are a sort of time lag of a first-order circuit. 12 We have introduced a suitable assumption for the module called the RC approximation such that the MEI term in Eq. (1) vanishes.…”
Section: Introductionmentioning
confidence: 99%
“…Using impedance spectroscopy and the RC approximation for the module, Eq. (1) can express the current (or heat) frequency dependence as 7,9,12 …”
Section: Introductionmentioning
confidence: 99%
“…2) A few methods using one sample have been proposed to estimate zT directly; the Harman and impedance spectroscopy (IS) methods are representative methods that employ this approach, wherein the Peltier heat Q P (= STI or STi ω , where I and i ω are the direct and alternating currents, respectively) is driven as a probe into the thermoelectric material with the current and can produce a temperature difference along the current direction. [3][4][5][6][7][8][9][10][11][12][13] Consequently, zT is estimated based on the Ohmic resistance and an additional resistance as a thermoelectric resistance, owing to the Peltier heat or temperature difference. Analyzing the model based on the non-steady-state heat equation, both methods are found to be identical in the time and frequency domains.…”
Section: Introductionmentioning
confidence: 99%
“…To characterize thermoelectric devices, Harman's method and power output measurements have been widely used to evaluate the ZT values and thermoelectric power, respectively, but additional extensive measurements are necessary to determine the three key parameters ( , S, and ). Recently, several studies have demonstrated that impedance spectroscopy can be used to determine the ZT values of thermoelectric bismuth telluride [29] and SKD [30,31] materials as well as bismuth telluride [32][33][34][35][36][37][38] and SKD [39,40] based devices. In a typical galvanostatic impedance spectroscopy measurement, a sinusoidal current perturbation drives the thermoelectric system slightly out of temperature equilibrium (appearance of a temperature gradient), inducing reorganization of the carriers owing to the Peltier effect, which allows the Seebeck voltage to be measured as a function of frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Most investigations using impedance spectroscopy for the characterization of bismuth telluride [29,32,34,35,38] and SKD [39,40] based thermoelectric devices have been performed at ambient temperature, with only a few studies reporting the properties of bismuth telluride based devices at operating temperatures up to 150 °C [33,37]. In this work, we employed impedance spectroscopy to elucidate the thermoelectric properties of an in-house-fabricated two-couple SKD-based device within the range of practical operating temperatures (23-450 °C) with the help of state-of-the-art mathematical models along with electrical, thermal, and microstructural characterization.…”
Section: Introductionmentioning
confidence: 99%